Three-dimensional spatial representation in freely swimming fish - Burt de Perera, Theresa; Holbrook, Robert I. (Cognitive processing, 2012)
Research on spatial cognition has focused on how animals encode the horizontal component of space. However, most animals travel vertically within their environments, particularly those that fly or swim. Pelagic fish move with six degrees of freedom and must integrate these components to navigate accurately—how do they do this? Using an assay based on associative learning of the vertical and horizontal components of space within a rotating Y-maze, we found that fish ( Astyanax fasciatus ) learned and remembered information from both horizontal and vertical axes when they were presented either separately or as an integrated three-dimensional unit. When information from the two components conflicted, the fish used the previously learned vertical information in preference to the horizontal. This not only demonstrates that the horizontal and vertical components are stored separately in the fishes’ representation of space (simplifying the problem of 3D navigation), but also suggests that the vertical axis contains particularly salient spatial cues—presumably including hydrostatic pressure. To explore this latter possibility, we developed a physical theoretical model that shows how fish could determine their absolute depth using pressure. We next considered full volumetric spatial cognition. Astyanax were trained to swim towards a reward in a Y-maze that could be rotated, before the arms were removed during probe trials. The subjects were tracked in three dimensions as they swam freely through the surrounding cubic tank. The results revealed that fish are able to accurately encode metric information in a volume, and that the error accrued in the horizontal and vertical axes whilst swimming in probe trials was similar. Together, these experiments demonstrate that unlike in surface-bound rats, the vertical component of the representation of space is vitally important to fishes. We hypothesise that the representation of space in the brain of vertebrates could ultimately be shaped by the number of the degrees of freedom of movement that binds the navigating animal.